Challenges and enablers for scaling up interventions targeting non-communicable diseases: a qualitative study applying the Consolidated Framework for Implementation Research to 19 research projects worldwide - Josefien van Olmen; Peter Delobelle; Meena Daivadanam; Hassan Haghparast-Bidgoli; Maria Lazo-Porras; J Jaime Miranda; Yuan Li; Rohina Joshi; Amanda G Thrift; Rajesh Vedanthan; Gina Agarwal; Mark D Huffman; et al. (BMJ Public Health)
Introduction Scaling up interventions targeting non-communicable diseases (NCDs) is a global health priority, and implementation research can contribute to that effort. In 2019, the Global Alliance for Chronic Diseases funded 27 implementation research studies to improve evidence for scaling up interventions targeting prevention and/or control of hypertension and/or diabetes in low-resource settings. We examined these studies to improve the understanding of the implementation factors, including challenges and facilitators, that influence the early implementation phase of scale-up research projects targeting NCDs.Methods This qualitative study was undertaken between August 2020 and July 2021. 43 semi-structured interviews were conducted with project investigators, implementers and policymakers, across 19 diverse scale-up projects, being implemented in 20 countries. The transcripts were inductively, open-coded using thematic analysis. Generated themes were mapped systematically to four out of five domain categorisations of the Consolidated Framework for Implementation Research (CFIR); the innovation domain fell outside the scope of this study.Results Highlighted findings using CFIR are: (i) outer setting: influence of politics, lack of coordination between government departments and differing agendas towards NCDs hindered implementation while reliable and trustworthy government connections proved useful; (ii) inner setting: commitment of resources for implementation was a challenge while research capacity, work culture and trustworthy networks facilitated implementation; (iii) individuals: high-level stakeholder support and leadership was essential; (iv) process: extensive time and efforts required for stakeholder engagement towards local contextualisation was challenging, while collaborating, joint reflection, effective communication and adaptation facilitated. COVID-19 provided both challenges and opportunities and these varied depending on the intervention characteristics and study objectives.Conclusion Researchers supporting the scale-up of complex interventions targeting NCDs need to leverage on existing trusting relationships and foster equitable stakeholder partnerships through research. Interpersonal skills and good communication are essential complements to research expertise and must be considered during capacity building.